2021
DOI: 10.3390/rs13214222
|View full text |Cite
|
Sign up to set email alerts
|

Camera Self-Calibration with GNSS Constrained Bundle Adjustment for Weakly Structured Long Corridor UAV Images

Abstract: Camera self-calibration determines the precision and robustness of AT (aerial triangulation) for UAV (unmanned aerial vehicle) images. The UAV images collected from long transmission line corridors are critical configurations, which may lead to the “bowl effect” with camera self-calibration. To solve such problems, traditional methods rely on more than three GCPs (ground control points), while this study designs a new self-calibration method with only one GCP. First, existing camera distortion models are group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The IO accuracy is also unfavorable when the network of images is built with only a few strips, which is typical for linear objects [ 11 ]. In those cases, the IO errors distort the EO, which leads to the so-called bowl effect [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IO accuracy is also unfavorable when the network of images is built with only a few strips, which is typical for linear objects [ 11 ]. In those cases, the IO errors distort the EO, which leads to the so-called bowl effect [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also for areas with low topographic diversity, a correlation between IOP and EOP is generated. This translates into the occurrence of a bowl effect [63,68]. In another study [69], it was shown that elimination of the bowl effect can be achieved by densifying the distribution of GCPs.…”
Section: Camera Calibrationmentioning
confidence: 99%
“…This effect is widely documented in the literature on close-range photogrammetry (e.g., [16,57,58]) and is the result of non-optimal self-calibration. Many studies have demonstrated the benefits of including oblique images in the image network to reduce these effects (e.g., [16,49,59,60]). Having at least one tilted camera therefore has the double advantage of collecting better images of the lateral faces of the coral heads in the axis of the trajectory, but also of optimizing the geometry of the image network to limit distortions as much as possible.…”
Section: Hermitage Backreef Zonementioning
confidence: 99%